2020
DOI: 10.9770/jesi.2020.7.3(24)
|View full text |Cite
|
Sign up to set email alerts
|

The effect of corporate governance structure on financial difficulties

Abstract: This study aims to examine the effect of Corporate Governance Structure (CG) and Corporate Social Responsibility (CSR) on Financial Difficulties. The contribution of this research is to explore the truth of CG goals and achieve quality CSR reporting and can provide solutions to conditions before and when companies experience financial difficulties and provide things that are considered important to anticipate the possibility of financial difficulties. CG in this study uses the size of the audit committee and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
5
1
Order By: Relevance
“…Other ESG reporting studies examine the context of the financially distressed firm. For instance, [44] uses Indonesia as one of the countries where some of its giant state-owned enterprises are experiencing financial difficulties. They find that ESG reporting is one approach that effectively prevents financial distress in Indonesian listed firms.…”
Section: Literature Review 21 Esg Reporting As Solution For Financial Distressed Firmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other ESG reporting studies examine the context of the financially distressed firm. For instance, [44] uses Indonesia as one of the countries where some of its giant state-owned enterprises are experiencing financial difficulties. They find that ESG reporting is one approach that effectively prevents financial distress in Indonesian listed firms.…”
Section: Literature Review 21 Esg Reporting As Solution For Financial Distressed Firmsmentioning
confidence: 99%
“…Lagged Variables ESG reporting studies are dominated by ones who focus on its impact, not the factor that determines the ESG reporting quality. For instance, firm performance [7,40,41] and risk of financial distress [11,44,45]. Thus, it will raise the causality issue that questions the "true" interested and dependent variables [38,63].…”
Section: Robustness Analysismentioning
confidence: 99%
“…Additionally, the studies by Sukma and Bernawati (2019), Andayani and Daud (2020), and Assad (2023) concluded that the audit committee size significantly influences the quality of the audit. Therefore, the audit committee size is expected to be correlated with the auditor's opinion, as Carcello and Neal (2000) and Alkilani et al (2019) found.…”
Section: Audit Committee Sizementioning
confidence: 99%
“…Slack resources Companies need to maintain their good name by disclosing information on CSR implementation to the public with regard to their concern for environmental aspects, labour, consumers, society, and the energy used in company operations to gain the trust of shareholders and stakeholders which will lead to company performance [5]. [6], [7] show a negative relationship between CSR and company performance.…”
Section: Introductionmentioning
confidence: 99%